2019
DOI: 10.1080/10749357.2019.1623458
|View full text |Cite
|
Sign up to set email alerts
|

A short bout of high-intensity exercise alters ipsilesional motor cortical excitability post-stroke

Abstract: Background: Acute exercise can increase motor cortical excitability and enhance motor learning in healthy individuals, an effect known as exercise priming. Whether it has the same effects in people with stroke is unclear. Objectives: The objective of this study was to investigate whether a short, clinically-feasible high-intensity exercise protocol can increase motor cortical excitability in non-exercised muscles of chronic stroke survivors. Methods: Thirteen participants with chronic, unilateral stroke partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 50 publications
(66 reference statements)
1
48
0
1
Order By: Relevance
“…Specifically, studies should further examine how exercise can be used as a motor rehabilitation strategy after neural injury. This would complement preliminary findings that exercise may help promote poststroke motor relearning 27 , functional recovery 44 , and neuroplasticity 45 .…”
Section: Discussionsupporting
confidence: 65%
“…Specifically, studies should further examine how exercise can be used as a motor rehabilitation strategy after neural injury. This would complement preliminary findings that exercise may help promote poststroke motor relearning 27 , functional recovery 44 , and neuroplasticity 45 .…”
Section: Discussionsupporting
confidence: 65%
“…Further, it is important to note that these data were obtained from healthy, low fit, young adults. Li et al [22] recently showed that fast treadmill walking increases MEPs from the lesioned hemisphere in those with chronic stroke. This suggests that high-intensity exercise is a feasible method to increase motor output in stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify exercise regimes that increase corticospinal excitability this population. Rehabilitation can capitalize on the post-exercise increases in corticospinal excitability, as this can prime the motor system for improvements in motor learning or re-learning [2,22].…”
Section: Introductionmentioning
confidence: 99%
“…Improved CV fitness was used in 13 of the studies (76%) (39,40,44,(50)(51)(52)(53). Changes to brain activity measured by an electroencephalogram (EEG) was reported in 5 (29%) of the 17 studies (47,50,(54)(55)(56).…”
Section: Desired Training Effectsmentioning
confidence: 99%